Perancangan Keselamatan dan Kesehatan Kerja dengan menggunakan Metode HIRARC di PT. X - Santoso, Demetrio Marvel; Kriswanto Widiawan (Jurnal Titra, 2022)
PT. X is a company engaged in the manufacturing industry that produces various kinds of wooden furniture products such as dining tables, chairs, cabinets, etc. PT. X was established in 2012 and during PT. X is running there are several accidents at work. This final project was carried out using the method of observation and interviews with field managers and workers. The purpose of this final project is to identify hazards, assess risks, and carry out risks to the company. After doing the analysis, in the production area of 16 sub-activities there are low risk rating categories with a total of 12 categories, a medium risk rating category with 21 categories, and a high risk rating category with a total of 7 categories. As for the warehouse area, there is a low risk rating category with a total of 2 categories and a medium risk rating category with a total of 4. It has been proposed 20 administrative engineering controls, 25 controls using personal protective equipment, and 1 control by technical design. If risk control is carried out, it is estimated that the risk rating will change to 0 extreme cases, 0 high cases, 12 moderate cases, and 34 low cases.